Transdermal Permeation and Skin Retention of Diclofenac and Etofenamate/Flufenamic Acid From Over-the-Counter Pain Relief Products - Kopečná, Monika; Kováčik, Andrej; Novák, Petr; Boncheva Bettex, Mila; Vávrová, Kateřina (Journal of pharmaceutical sciences, 2021)
Topical pain relief products differ in the type of drug, concentration, and formulation. All these factors influence the drug transit through the skin barrier, and its eventual retention in the skin as a reservoir for subsequent release. In addition, the drug potency can be different, which is important for the product efficacy. We studied here ex vivo human skin permeation and retention of five over-the-counter NSAID gels containing 2.32% diclofenac (DIC) and 5-10% etofenamate (ETF). The potency of the permeated/retained drug amounts were compared using a composite parameter, the Index of Relative Topical Anti-inflammatory Activity (IRTAA), which is calculated as the product of the skin permeation/retention and the drug relative potency. The IRTAAs of the DIC gel were 94-667-fold higher and 72-208-fold higher for transdermal delivery and skin retention, respectively, than IRTAAs of the ETF gels. These superior IRTAAs indicate that DIC delivered by this topical formulation would achieve a higher bioactivity and would form a potent drug reservoir relevant for its subsequent long-lasting release.
Keywords: Gels; Drug delivery system(s); kyselina flufenamová; permeabilita; Percutaneous; Transdermal; aplikace kožní; Diclofenac; Pain; Anti-Inflammatory Agents, Non-Steroidal; Permeability; antiflogistika nesteroidní; bolest; Formulation; lidé; Skin; Humans; Flufenamic Acid; kožní absorpce; diklofenak; Skin Absorption; gely; Absorption; Administration, Cutaneous